2023
DOI: 10.3390/math11092102
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Hybrid Mixed Two-Point Step Size Gradient Algorithm for Solving Non-Linear Systems

Abstract: In this paper, a two-point step-size gradient technique is proposed by which the approximate solutions of a non-linear system are found. The two-point step-size includes two types of parameters deterministic and random. A new adaptive backtracking line search is presented and combined with the two-point step-size gradient to make it globally convergent. The idea of the suggested method depends on imitating the forward difference method by using one point to estimate the values of the gradient vector per iterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Accordingly, many authors have suggested several modificationsof the classical methods that deal with optimization problems, e.g, the Newton method [3], the quasi-Newton method [4], the semi-gradient method [5], the hybrid gradient meta-heuristic algorithm [6,7], and the CG-method [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many authors have suggested several modificationsof the classical methods that deal with optimization problems, e.g, the Newton method [3], the quasi-Newton method [4], the semi-gradient method [5], the hybrid gradient meta-heuristic algorithm [6,7], and the CG-method [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%